Avaliação da carbonatação em materiais cimentícios com substituição de cimento Portland por cinza do bagaço da cana-de-açúcar - Pletsch, Alexander (Universidade do Vale do Rio dos Sinos, 2019)
Portland cement is recognized as an important construction product worldwide, but in clinker production there is a high CO2 emission in the atmosphere. In order to reduce these rates, research has been carried out to use alternative materials, similar to Portland cement. Brazil is the largest producer of sugar cane in the world, and with the processing of this plant, the products of sugar, ethanol and derivatives are generated. The beneficiation process generates sugarcane bagasse as waste. The bagasse burning process generates an ash, known as sugarcane bagasse ash (SBA). The ash, in most cases, is rich in silica and may be present in crystalline form, having inert properties and not being attractive for its replacement by cement but rather by replacement of fine aggregate, but also in amorphous form, which in contact with with cementitious composites reacts with hydration products, characteristic of a pozzolan. In this study, the evaluation of the mechanical properties and durability of reference mortar and with SBA substitution contents of Portland cement of 5%, 10% 20% and 30% with 3 water / binder ratios: 0.4, 0 0.5 0.6. The research aims to evaluate the mechanical strength and durability of this concrete with SBA, with emphasis on carbonation. For this, accelerated carbonation tests had ben performed, evaluating the behavior of SBA in the new cementitious composites. It is concluded that the ash helps in the improvement of mechanical properties, by pozzolanic effects and by the filler effect, in the content of up to 20% of substitution. The carbonation front for substitution contents of up to 20% suffers a slight difference from the reference. The 30% content presented a mechanical resistance and a higher carbonation compared to the others.
Keywords: Cinza do Bagaço da Cana-de-Açúcar (CBC); Pozolanas; Carbonatação; Sugarcane bagasse ash (SBA); Pozzolans; Carbonation; ACCNPQ::Engenharias::Engenharia Civil